Effect of the physiological stress in two species of ants (Formicidae) that inhabit coffee plantations with and without shade - VARGAS O., GERMÁN A.; RIVERA, LEONARDO F.; ARMBRECHT, INGE (Revista Colombiana de Entomología, 2006)
It has been found that ant biodiversity is reduced with the transition from traditional coffee plantations (shade) to intensified (sun) systems and also that the composition of ant species changes in coffee plantations according to management. It has been hypothesized that ants from sun coffee plantations have physiological adaptations that permits them to colonize these habitats in comparison with ants from shade plantations. Using temperature as an indicator of microclimatic fluctuation, the behavior of Tetramorium simillimum, exclusive to sun plantations, and of Paratrechina steinheili, abundant but not exclusive to shade plantations (in Apía, Risaralda, Colombia), were analyzed in two thermal fluctuation tests between 17ºC and 32ºC, and one thermal shock test (12ºC and 35ºC) in an environmental chamber. Control colonies were maintained at constant temperature (24 +/1ºC). Ant activity outside the nest, foraging and mortality were evaluated. In the first two tests P. steinheili exhibited a relatively lower mortality than T. simillimum. In both cases the colonies submitted to stress in the environmental chamber lost more workers than controls. In the thermal shock test an increase in P. steinheili mortality was found, but it did not exceed that of T. simillimum. It is concluded that there is no evidence for physiological adaptation, at least detectable, of T. simillimum to thermal stress in comparison to P. steinheili and that perhaps other ecological factors, such as limitation of nesting resources, may restrict the presence of the latter to sun coffee plantations.